2007
DOI: 10.1038/sj.bjc.6603692
|View full text |Cite
|
Sign up to set email alerts
|

High-level amplification at 17q23 leads to coordinated overexpression of multiple adjacent genes in breast cancer

Abstract: Increased copy numbers of 17q23 chromosomal region have been shown to occur in different tumour types and to be associated with tumour progression and with poor prognosis. Several genes have earlier been proposed as potential oncogenes at this region largely on the grounds of cell lines studies. In this study, we performed a systematic gene expression survey on 26 primary breast tumours with known 17q23 amplification status by quantitative real-time reverse transcriptase-polymerase chain reaction (RT-PCR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…We observed that 9% to 64% of genes located in the regions had associated overexpression. This is in line with other studies reporting that highly amplified regions contain a number of overexpressed genes (Hyman et al, 2002;Garcia et al, 2005;Parssinen et al, 2007). In concordance with our data, Snijders et al (2005) detected narrow amplifications at 6q12 (PTP4A1, EGFL11), 9p13.3 (TLN1), 9p24.1 (UHRF2, JMJD2C, PTPRD), and 11p13 (CD44, FJX1, TRAF6) in oral SCC (OSCC) using BAC arrays and confirmed the expression levels of selected genes using Q-RT-PCR.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that 9% to 64% of genes located in the regions had associated overexpression. This is in line with other studies reporting that highly amplified regions contain a number of overexpressed genes (Hyman et al, 2002;Garcia et al, 2005;Parssinen et al, 2007). In concordance with our data, Snijders et al (2005) detected narrow amplifications at 6q12 (PTP4A1, EGFL11), 9p13.3 (TLN1), 9p24.1 (UHRF2, JMJD2C, PTPRD), and 11p13 (CD44, FJX1, TRAF6) in oral SCC (OSCC) using BAC arrays and confirmed the expression levels of selected genes using Q-RT-PCR.…”
Section: Discussionsupporting
confidence: 92%
“…The 17q23-q25 neighboring region can be divided into two regions, 17q21-23 and 17q25, by sliding mean analysis. The 17q21-23 region coincides with a core amplicon identified in breast tumors compared to normal tissue [27]. 20q13 amplification has been associated with poor prognosis [28] and has been validated in several studies [29] while 20q11 gain has not previously been reported to have prognostic meaning independent of 20q13.…”
Section: Regions Of Differential Expressionmentioning
confidence: 80%
“…RPS6KB1, PAT1, and TBX2 were also found coamplified in 10% of tumors (41). A recent study of primary breast tumors revealed that overexpression of 11 genes in the region of 54.5 to 56.1 Mb (FAM33A, DHX40, CLTC, PTRH2, TMEM49, TUBD1, RPS6KB1, ABC1, USP32, APPBP2, and PPMD1) is activated by high level of amplification and was not observed with low-level copy number gain (42). These data are in agreement with our finding that, although gain in the region was common (by moving average), only distinct amplification detectable by the segmentation algorithm was associated with prognostic variables.…”
Section: Discussionmentioning
confidence: 99%